Biogenic synthesis of silver nanoparticles using Polygonum Minus fresh and dried leaves extract and its antibacterial and antioxidant properties - Mohd Amin, Nor Amaiza; Ibrahim, Nurhanis Najihah; Kadir Basha, Roseliza; Samsu Baharuddin, Azhari (HH Publisher, 2024)
Research reveals that techniques for producing silver nanoparticles through plant-mediated synthesis exhibit potent antimicrobial properties. The purpose of this work is to evaluate the antibacterial capabilities of silver nanoparticles made with leaf extract from Polygonum Minus (Kesom) as the reducing agent. The visual color changes observed the formation of PM-AgNPs and UV-Vis Spectrophotometry was used to validate the production of PM-AgNPs, displaying an absorption peak at about 440 nm. Subsequent characterization using X-ray diffraction (XRD) analysis and Fourier Transform Infrared (FTIR) Spectroscopy revealed the presence of biomolecules from the leaf extract that were in charge of creating PM-AgNPs and determining their crystalline nature. Results from the disc diffusion showed that PM-AgNPs inhibited the growth of Gram-negative and Grampositive bacteria.